Geometric origin of intrinsic spin hall effect in an inhomogeneous electric field - Zhang, Anwei; Rhim, Jun Won (Communications Physics, 2022)
In recent years, the spin Hall effect has received great attention because of its potential application in spintronics and quantum information processing and storage. However, this effect is usually studied under the external homogeneous electric field. Understanding how the inhomogeneous electric field affects the spin Hall effect is still lacking. Here, we investigate a two-dimensional two-band time-reversal symmetric system and give an expression for the intrinsic spin Hall conductivity in the presence of the inhomogeneous electric field, which is shown to be expressed through the geometric quantities: quantum metric and interband Berry connection. We show that for Rashba and Dresselhaus systems, the inhomogeneous intrinsic spin Hall conductivity can be tuned with the Fermi energy. On the other hand, when people get physical intuition on transport phenomena from the wave packet, one issue appears. It is shown that the conductivity obtained from the conventional wave packet approach cannot be fully consistent with the one predicted by the Kubo-Greenwood formula. Here, we attempt to solve this problem.
Keywords: Homogeneous electric field; Inhomogeneous electric fields; Intrinsic spin; Intrinsic spin hall conductivities; Quantum information processing; Quantum information storage; Symmetric systems; Time-reversal; Two bands; Two-dimensional